Review Of Islamic Law In The Shafi‘i School And The Hanafi School On The Marriage Contract Of Persons With Speech Impairment - Rokhmat2; Eko Wahyu Susilo; EkoSariayekti (Yayasan Azhar Amanaa Yogyakarta, 2024)
This article examines the practice of marriage contracts for individuals with speech disabilities (tunawicara) from the perspective of Islamic Law, particularly according to the Shafi‘i and Hanafi schools of thought, as well as Indonesian legislation as outlined in the Compilation of Islamic Law (KHI). The focus of this study arises from the issue of ijab (offer) and qabul (acceptance), which must be performed consecutively without a long pause, as any interruption or inability to speak may affect the validity of the marriage contract. This study aims to analyze the legal status of marriage contracts involving speech-impaired individuals according to both schools of Islamic jurisprudence and to explore the basis of maslahah (public interest) in establishing the law. This research employs a qualitative method using a library research approach. Data were collected from books, journals, and other relevant literature, and then analyzed descriptively to explain legal concepts and draw conclusions. The results show that both the Shafi‘i and Hanafi schools permit the marriage contract of a speech-impaired individual through writing or gestures. However, the two differ in their legal approaches: the Shafi‘i school applies qiyas, equating spoken words, writing, and gestures, while the Hanafi school applies istihsan, considering gestures not fully equivalent to writing. Therefore, gestures are only permitted when the speech-impaired individual is unable to write.